Cryptic diversity in the Hypsiboas semilineatus species group (Amphibia, Anura) with the description of a new species from the eastern Guiana Shield - Fouquet, Antoine; Martinez, Quentin; Zeidler, Lauren; Courtois, Elodie A.; Gaucher, Philippe; Blanc, Michel; Lima, Jucivaldo Dias; Souza, Sergio Marques; Rodrigues, Miguel T.; Lima, Jucivaldo Dias; Souza, Sergio Marques; Rodrigues, Miguel T.; et al. (Zootaxa, 2016)
We used molecular and morphological data to investigate the hidden diversity within the Hypsiboas semilineatus species group, and more specifically within H. geographicus, an allegedly widespread species in northern South America. As a result, the identity of H. geographicus was clarified, several candidate species were detected and one of them, from the eastern Guiana Shield, is described herein as a preliminary step to resolve the taxonomy of the group. Hypsiboas diabolicus sp. nov. is mainly distinguished from closely-related species by an acuminate snout in lateral view, well-developed webbing between fingers and toes, and unspotted carmine/crimson colouration on the concealed surfaces of legs, feet and hands in life. The tadpole of the new species is described and is characterized by a large A-2 gap, a mostly single row of large marginal papillae, and a dark brown to black colouration. We also describe the advertisement call of the new species, which is defined as a soft call consisting of short clusters of 2–3 chuckles with a dominant frequency ranging between 1.11–1.19 kHz. Hypsiboas diabolicus sp. nov. is currently known only from the eastern Guiana Shield, and is probably endemic to that region. The new species’ range overlaps broadly with another candidate species referred to as H. aff. semilineatus 1. Our preliminary results stress out a high cryptic diversity in that species group and the need for a formal redescription of Hypsiboas geographicus based on more topotypic material than what is currently available to properly sort out the taxonomic status of several lineages in that clade.